1995
DOI: 10.1149/1.2048476
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methoxylation of Porous Silicon Surface

Abstract: An electrochemical process aiming at the grafting of methoxy groups on the hydrogenated porous silicon surface at room temperature has been designed. This takes place through partial anodic dissolution of porous silicon in anhydrous methanol. A dissolution mechanism is proposed by analogy with that of the anodic dissolution of ~ilicon in aqueous fluoride media. The methoxylated surface exhibits improved optical characteristics (increased photolun~nescence efficiency, blue shift of the emission), similar to por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
98
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 1 publication
14
98
0
Order By: Relevance
“…In the case of VFC, which is a solid with a low melting T (323 K), hydrosilylation can be obtained by formation of Si radicals through Si-H homolysis, activated via UV-or visible-light exposure, or by heating. Alternative, more elaborate methods have been proposed for alkenes, as halogenation of the surface [8], thermal reaction of Grignard compounds [15], activation of the surface by radicals [6], electrochemistry [11,32]. In the present study, an effort has been made to explore a simple, reproducible and mild anchoring route, which implies, i.a., to expose the H-terminated Si(1 0 0) surface only to one chemical during the delicate phase of anchoring.…”
Section: Resultsmentioning
confidence: 97%
“…In the case of VFC, which is a solid with a low melting T (323 K), hydrosilylation can be obtained by formation of Si radicals through Si-H homolysis, activated via UV-or visible-light exposure, or by heating. Alternative, more elaborate methods have been proposed for alkenes, as halogenation of the surface [8], thermal reaction of Grignard compounds [15], activation of the surface by radicals [6], electrochemistry [11,32]. In the present study, an effort has been made to explore a simple, reproducible and mild anchoring route, which implies, i.a., to expose the H-terminated Si(1 0 0) surface only to one chemical during the delicate phase of anchoring.…”
Section: Resultsmentioning
confidence: 97%
“…The proposed attachment mechanism is the same as that for HGC surfaces proceeding via formation of an aryl radical which abstracts H from the surface producing a Si radical which couples with a second aryl radical giving a Si±C bond. Less well-characterized is the procedure of electrochemically oxidizing H-terminated porous Si in the presence of anhydrous methanol [51]. A methoxylated Si surface results and the reaction is presumed to involve initial formation of a Si radical.…”
Section: Some Related Modi®cation Methodsmentioning
confidence: 99%
“…They showed that under anodic polarization, methoxy-terminated surfaces (RSi-OCH 3 and QSi-(OCH 3 ) 2 can be prepared. 192 The aryl diazonium approach benefits from the low cathodic overpotentials necessary to generate aryl radicals X-Ar-N 2 + + e À -X-Ar + N 2 (X = NO 2 , Br, COOH, CN)…”
Section: Lewis Acid-catalyzed Hydrosilylation Reactionsmentioning
confidence: 99%